Chronic inflammation and gut microbiota at a glance: Insights into fertility barriers - Winarno, Bondan; Albright, Ivan Angelo; Tjahyono, Evi; Adamas, Muhammad; Poli, Januar Alfred; Supardi, Supardi (Universitas Airlangga, 2024)
The acrosome reaction (AR) is a crucial step in fertilization, enabling sperm to penetrate the oocyte's protective layers, but various elements can hinder AR. Fertilization is a fundamental process in mammalian reproduction, involving the fusion of a sperm with oocyte. To achieve this, sperm must undergo capacitation, a series of biochemical changes that prepare them for fertilization. Once capacitated, sperm can penetrate the protective layers of the oocyte, after capacitation, sperm bind to receptors on the zona pellucida (ZP), a protective layer surrounding the egg. This binding triggers the acrosome reaction (AR), releasing enzymes that help the sperm penetrate the protective layers. Once the sperm has penetrated, it fuses with the oocyte's plasma membrane, delivering its genetic material. Anti-sperm antibodies (ASA) can directly bind to sperm, hindering their function and ability to undergo AR. Chronic inflammation, often associated with conditions like diabetes and obesity, with chronic hyperglycemia producing advanced glycation end products (AGEs) can create a pro-inflammatory environment that negatively impacts sperm parameter and function. Additionally, gut microbiota (GM) dysbiosis has been linked to chronic inflammation and may contribute to infertility. Proper AR is essential for successful fertilization, but presence of ASA, GM dysbiosis, and chronic inflammation may hinder fertility. The evidence suggests improving inflammation by proper GM symbiosis may improve sperm parameter and fertility.